Evaluation of Performance Program in Tirta Wahana Swimming Club, Grobogan Regency (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This study aims to evaluate the antecedents, transactions, and outcomes in the swimming achievement training program at Tirta Wahana Club, Grobogan Regency. This study uses a descriptive qualitative approach to the Countenance Stake evaluation model. The subjects in this study were administrators, coaches, and athletes at Tirta Wahana Club in Grobogan Regency. The results of this study are Antecedent the implementation of swimming coaching in Tirta Wahana Club is going well, the availability of facilities and infrastructure of Tirta Wahana Club is well available, availability of human resources in recruiting coaches and athletes seems simple, and funding comes from 2 elements, Transaction (process) swimming coaching at Tirta Wahana Club, Grobogan Regency consisting of aspects of the implementation of training programs, coordination, consumption, welfare, and transportation have been carried out well based on data, and facts on the ground. The outcome is coaching at the Tirta Wahana Club has increased performance in following the championships at the provincial level in Central Java, and nationally. The conclusion of this study is the overall antecedent, transaction, outcome development of the swimming achievement of the Tirta Wahana Club in Grobogan Regency has been going well with the revision of aspects in the coaching program so that it can advance the coaching system, and improve achievement.